DEVELOPMENT OF A GOOGLE FORM-BASED THREE TIER DIAGNOSTIC TEST INSTRUMENT TO IDENTIFY MISCONCEPTIONS OF GRADE VII STUDENTS ON THE THEME OF HEAT AROUND US - Komala Dewi; Sjaifuddin Sjaifuddin; Mudmainah Vitasari (Jurnal IPA Terpadu, 2024)
Understanding a concept is very important for students to understand, but in the process misconceptions often occur. To minimize misconceptions, an instrument is needed that can diagnose student misconceptions through diagnostic test assessments. The purpose of this study is to assess the level of validity and ensure the use of a Google form-based three-tier diagnostic test. This instrument can identify the misconceptions of seventh grade junior high school students on the theme of heat around us. This development research refers to the three steps of the Thiagarajan model: defining, designing, and developing. Expert validators and samples, namely 2 lecturers as assessment experts participated in this study, 1 lecturer as a media expert, and 3 practitioners, as well as 30 seventh grade junior high school students. Interview sheets, validation, limited trials and teacher response questionnaires were used in data collection. The percentage calculation results obtained a score of 89.9% with a very valid category. The results of the limited trial showed that 83.4% of students had misconceptions, 12.3% knew the concept, and 4.3% did not know the concept. While the results of the teacher response questionnaire showed that 84.6% of the test were in the very high category.